Exploring Teachers' Perspectives On The Challenges Of Teaching Mathematics In The Intermediate Phase Schools In South Africa - Agyeman Nana Yaw Brenya; Makhoba Thami Isaac; Avela Ngqunguza; Nqoma Lungile; Mtsi Nomxoliswa; Chiphambo Shakespear (Pendidikan Matematika Universitas Muhammadiyah Bangka Belitung, 2025)
The study explored teachers' perceptions of the challenges that affect mathematics instruction in the intermediate phase schools in the Chris Hani District. The study aims to explore teachers' perspectives on the challenges of mathematics instruction in the intermediate phase schools in South Africa. This study is important because it focuses on the personal and contextual factors that hinder effective mathematics teaching. The study seeks to understand teachers' perceptions and contextual factors that affect the effective teaching of mathematics in intermediate-phase schools to provide interventions. A qualitative approach with a phenomenology design was used to explore the objective of the study. The phenomenology design focused on understanding the lived experiences of the participants and their cultural and social contexts. The study used purposive sampling to select 8 participants with significant experience in teaching in the intermediate phase schools. The study found semi-structured interviews useful in collecting data because they blend flexibility and open-ended questions to gain insight. Thematic data analysis was used to analyse themes and patterns that emerged within the collected data. A major result was the inability of teachers to address the individual needs of students. In addition, teachers expressed concern about the curriculum expectations and the need for reforms. This study shows that, given the necessary support, they can improve mathematics teaching. However, the challenges to mathematics teaching suggest the need for the implementation of measures to improve mathematics teaching. Recommendations of the study include the need for teacher development in mathematics education and the need for education authorities to embark on curriculum reforms to address teachers' concerns regarding workload. In addition to improving mathematics teaching, policymakers prioritise educational reforms to address systemic challenges that affect mathematics instruction. This study contributes to understanding the challenges that affect mathematics teaching.